Genomic DNA Extraction Protocol for Artemisia Annua L. Without Using Liquid Nitrogen and Phenol - Agrawal, Ankit; Sharma, Anjana; Shukla, Narmada Prasad (International Journal of Applied Sciences and Biotechnology, 2017)
Artemisia annua is an important medicinal plant, used for curing various diseases especially malaria. It secretes verities of secondary metabolites which hinders in the DNA extraction. This investigation describes an efficient DNA extraction protocol for A. annua based upon the Cetyl Trimethyl Ammonium Bromide (CTAB) extraction method without using hazardous chemicals i.e. liquid nitrogen and phenol. The developed protocol is simple, reliable and operative in normal laboratory condition yielding intact DNA having good quantity (502.7 to 1288.5 ng/µl) and quality (A260/280 ratio - 1.82 to 1.85) in two working days. Proper amplification of extracted DNA indicates its suitability for the various molecular biological applications. Int J Appl Sci Biotechnol, Vol 4(4): 448-451